1993
DOI: 10.1007/bf03164966
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up studies on Iodine-131 treatment of hyperthyroid graves’ disease based on the measurement of thyroid volume by ultrasonography

Abstract: In the present series of studies, the long-term (four year) effect of 80 Gy of 131I treatment was evaluated in patients with hyperthyroid Graves' disease whose thyroid volumes have been accurately estimated with a high resolution ultrasound scanner. One year after 131I treatment, 23.1% (3 out of 13 patients) remained hyperthyroid, 69.2% (9 out of 13) became euthyroid, and 7.7% (1 out of 13) were in a hypothyroid state. Since three patients in a hyperthyroid state one year after treatment were subsequently trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…In Italy, a country with a low iodine intake, Chiovato et al [19] demonstrated a significant reduction in thyroid volume one year after 131 I treatment, but this not was investigated afterwards. The lack of influence of pretreatment thyroid volume on the outcome of 131 I treatment has also been reported by other study [20]. Table 2 Thyroid volume (mean SD) and its reduction after 131 I or spontaneous remission (expressed in ml and percentage of reduction respectively)…”
Section: Discussionsupporting
confidence: 72%
“…In Italy, a country with a low iodine intake, Chiovato et al [19] demonstrated a significant reduction in thyroid volume one year after 131 I treatment, but this not was investigated afterwards. The lack of influence of pretreatment thyroid volume on the outcome of 131 I treatment has also been reported by other study [20]. Table 2 Thyroid volume (mean SD) and its reduction after 131 I or spontaneous remission (expressed in ml and percentage of reduction respectively)…”
Section: Discussionsupporting
confidence: 72%
“…22 Therefore, it is reasonable to consider an effect of thyroid volume on therapy outcomes. Most studies in humans have not found any relationship between thyroid gland size and a hypothyroid outcome, [23][24][25] although one study reported that smaller goitres were a risk factor for developing hypothyroidism. 26 Thyroid size estimation by palpation, as a scoring factor Effect of thyroid volume on radioiodine therapy outcome in hyperthyroid cats Veerle Volckaert 1 , Eva Vandermeulen 1 , André Dobbeleir 2 , Luc Duchateau 1 , Jimmy H Saunders 1 …”
Section: Introductionmentioning
confidence: 99%
“…Dose calculations, where utilized, are extremely variable (75-200 µCi/ g) (12,17) , even at a same health center, especially in relation to goiter volume, hyperthyroidism severity and presence of cardiopathy. The utilization of ultrasonography in the measurement of goiter volume is of little practical significance and does not make any difference in the final effect of TD as compared with the clinical evaluation (31) . Although it is seemingly non-practical, a simple methodology was recently described for biokinetic evaluation of radioactive iodine as well as the evaluation of the absorbed dose/administered activity ratio (32) , that might be useful for more effective dose calculations.…”
Section: Discussionmentioning
confidence: 99%